Immunogenic and immunotolerogenic effects of extracorporeal photopheresis in high immunological risk kidney recipients. A single center case series. Issue 3 (22nd December 2021) - Xipell, Marc; Molina‐Andújar, Alícia; Cid, Joan; Piñeiro, Gastón J.; Montagud‐Marrahi, Enrique; Cofan, Frederic; Oppenheimer, Frederic; Rovira, Jordi; Diekmann, Fritz; Lozano, Miquel
Abstract: The immunomodulatory effects of extracorporeal photopheresis (ECP) have been used for the treatment of T‐cell mediated disorders, such as rejection in organ transplantation. Currently, it is an established therapy for heart and lung rejection, but not for kidney transplantation (KT), where experience is limited. In addition, some data suggest that ECP could generate an immune response against infections, thus being an alternative for the treatment of rejection in case of active or high‐risk of infection. In the present study, we analyze four cases of use of ECP as concomitant therapy in patients with KT and high risk of opportunistic infections due to the high burden of immunosuppression throughout their renal diseases. Two patients had concomitant viral infection (cytomegalovirus and BK virus, respectively) and three patients were on treatment for graft rejection. In the two patients with active viral infection, the infection was successfully controlled during ECP treatment. In all cases, ECP has been shown to be a safe procedure, without complications.